Learning Online : The Student Experience - Veletsianos, George (Book collections on Project MUSE., 2020)
"This book presents a series of case studies capturing the variety of student experiences with online learning. The book is original in assessing the lived experience of online learning from students' perspectives by using qualitative data to supplement quantitative analytics"--